Entanglements, Nature, and Inequalities in the Darien: Analyzing Interoceanity in Panama and Colombia (2015)
This essay explores the spatial turn in global history by analyzing portals of globalization, literature on the territorialism of capitalism, megaprojects as mechanisms of displacement, interoceanity, and postcolonial approaches to environmental history. The historical case of the Panama Canal and the contemporary proposals for a dry canal in Colombia are employed. The essay evidences its position with secondary sources, newspaper articles, NGO reports, and media sources. The results reveal that megaprojects for interoceanity include complex entanglements of actors and ideas about nature and local populations. The imperial role of the U.S. is key to understanding the emergence and construction of the Panama Canal. Even so, studies of the contemporary enlargement of the Canal include the interplay of other factors, such as patriotism and conservation policies used by the Panamanian government and enterprises to support interoceanity. The Colombian case reveals contradictions between the policies that grant territorial rights to local communities identifying them as forest stewards and those that seek capital support from China to construct a dry canal. Within neoliberal globalization, there is a trivialization of environmental ends and policies that has been articulated to coordinate with the construction of megaprojects.